Analisis Pengendalian Kualitas Menggunakan Metode Statistical Process Control (SPC) Pada Part Lever Comp Throttle Di PT.OMI - Dira Santana; Azizah, Fahriza Nurul (Fakultas Teknik Universitas Tulang Bawang, 2024)
PT. OMI is a company that operates in the automotive industry in the Karawang area, the goods it produces are very varied and have quite a lot of customers. To increase customer trust, customer satisfaction is the most important thing, with the aim of knowing the process and quality results of a product by using a p-control chart and knowing the various types of defects that occur in the product. The research uses data collection methods in the form of production data as well as product defect data produced and data processing using p control charts and Minitab software to analyze the causes of types of defects and provide suggestions for companies. The results of production quality control in 2022 samples were obtained CL (Middle limit) is 0.0077%, LCL (Lower limit) is 0.0074% and UCL (Upper limit) is 0.0080%. From the analysis, there are 3 types of defects, namely color defects at 48%, chip defects at 40%, and finally burry defects at 12%. Problems occur due to several causes such as human factors, machines, methods, and materials. To solve these problems, a fishbone diagram was created. Product control at PT OMI is under controlled conditions. Keywords: Control Chart, Defect, Quality